2014
DOI: 10.1098/rstb.2013.0150
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the two-way signalling route from synapses to the nucleus, and from the nucleus back to the synapses

Abstract: During learning and memory, it has been suggested that the coordinated electrical activity of hippocampal neurons translates information about the external environment into internal neuronal representations, which then are stored initially within the hippocampus and subsequently into other areas of the brain. A widely held hypothesis posits that synaptic plasticity is a key feature that critically modulates the triggering and the maintenance of such representations, some of which are thought to persist over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…While the precise signaling cascades involved in Arc transcription are not well defined, one study has shown that PKA/MAPK cascades regulate Arc expression ( Waltereit et al, 2001 ) and that the MAPK/CREB pathway is also essential for Arc expression ( Ying et al, 2002 ; Nonaka et al, 2014 ). Given the impaired ERK1/2 and pCREB in postnatal ethanol-exposed neonatal mice, Arc protein levels were also significantly reduced in ethanol-exposed neonatal as well as adult mice and blockade or genetic deletion of CB1R prior to P7 ethanol treatment–restored Arc protein levels in neonatal and adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…While the precise signaling cascades involved in Arc transcription are not well defined, one study has shown that PKA/MAPK cascades regulate Arc expression ( Waltereit et al, 2001 ) and that the MAPK/CREB pathway is also essential for Arc expression ( Ying et al, 2002 ; Nonaka et al, 2014 ). Given the impaired ERK1/2 and pCREB in postnatal ethanol-exposed neonatal mice, Arc protein levels were also significantly reduced in ethanol-exposed neonatal as well as adult mice and blockade or genetic deletion of CB1R prior to P7 ethanol treatment–restored Arc protein levels in neonatal and adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Arc's role in multiple bi-directional plasticity pathways [14][15][16], it is possible that the sustained presence of Arc in the vicinity of synapses can modulate the response to further patterns of stimulation. This molecular "priming" of activated synapses could conceivably lead to distinct functional outcomes in granule cell circuits relative to pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, LTP induction leads to the synthesis and specific localization of Arc/Arg3.1 in non‐potentiated synapses, a phenomenon described as an inverse‐tagging mechanism . Synaptic recruitment of Arc/Arg3.1 to inactive synapses was due to a preferential interaction between the inactive form of CaMKIIβ and Arc/Arg3.1 and it may represent a mechanism by which neurons increase contrast and prevent undesired enhancement at non‐stimulated synapse . It remains to be addressed the spatial rules of the inverse tagging.…”
Section: Actin Camkii and The On‐going Dynamics Of Synapsesmentioning
confidence: 99%